The Role of Perceived Social Support in the Association Between Stressful Life Events and Suicidal Behavior - Panesar, Balpreet; Rosic, Tea; Rodrigues, Myanca; Sanger, Nitika; Baptist-Mohseni, Natasha; Hillmer, Alannah; Chawar, Caroul; D'Elia, Alessia; Minuzzi, Luciano; Thabane, Lehana; Samaan, Zainab (Frontiers in Psychiatry, 2021)
Background Suicide is a serious public health concern for which there have been well-established protective and risk factors reported in literature. There is a lack of evidence on the indirect effects of other variables on these factors. Specifically, the association between stressful life events and suicidal behaviour may be affected by perceived social support, but the nature of the role of perceived social support in this association is largely uninvestigated. Objectives Thus, this paper aims to explore the role of perceived social support in the association between stressful life events and suicidal behaviour. Perceived social support will be explored as a mediator and as a moderator in this association. Methods Data were obtained from the Determinants of Suicidal Behaviour Conventional and Emergent Risk (DISCOVER), a study conducted to identify risk factors of suicidal behaviour. The study participants are individuals with suicide attempts admitted to hospital. Suicidal behaviour was measured using two outcomes 1) the occurrence of a suicide attempt 2) level of suicide intent as measured by the Pierce Suicide Intent Scale. Results Stressful life events were significantly associated with suicide attempts (OR 1.440, CI 1.440, 1.682, p <0.001) and perceived social support (B -0.785, CI -1.501, -0.068, p 0.032). There was no significant mediation effect by perceived social support in the association between stressful life events and suicide attempts (Sobel’s test statistic 1.64, p 0.100). Perceived social support did not moderate the relationship between stressful life events and suicide attempts ((OR 1.007, CI 0.987, 1.027, p 0.514) or the relationship between stressful life events and level of suicidal intent (B -0.043, CI -0.132, 0.046, p 0.343). Conclusion Stressful life events are associated with increased risk of suicide attempts. The study also identified an inverse relation between stressful life events and perceived social support. These associations were independent of perceived social support. This study highlights the effects of stressful life events on suicide risk is not affected by perceived social support requiring further investigation onto measures to reduce the impact of social stressors on people with risk of suicide.